Pengembangan Website Promosi Digital UMKM SABANA Kebab & Burger - Athari Mahdafikia; Zico Phalestine; Rahmat Hidayat; Novadilastri .; Sularno . (CV. ITTC INDONESIA, 2026)
The rapid development of information technology has driven the utilize of digital media as an effective promotional tool across various business sectors, including Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector. SABANA Kebab & Burger, located in Pasar Kuliner Padang Panjang, is a potential fast-food culinary business. However, constraints in digital marketing implementation have caused its promotional outreach to remain traditional and geographically restricted. This study aims to design a business website as a digital promotional medium to extensively present the profile and products of SABANA Kebab & Burger, thereby improving business visibility and competitive edge. This research applied a descriptive qualitative method integrated with a Project-Based Learning (PBL) approach. Data collection techniques involved direct field observation, semi-structured interviews with the business owner, Mr. Imam Suhada, and visual documentation. The website was developed using the Strikingly web-builder platform by structuring essential pages including the homepage, product catalogs, company profile, operational location, and ordering contacts. The research output indicates that the designed website has been fully published and operates as an accessible digital information center. The existence of this website is expected to expand market outreach, build a professional business image, and accelerate sustainable sales growth for the culinary MSME